2019
DOI: 10.1590/s1980-220x2018009703439
|View full text |Cite
|
Sign up to set email alerts
|

Representations of people living with HIV: influences on the late diagnosis of infection

Abstract: Objective: To analyze the representations constructed by people living with HIV on the infection and their influence on the late search for diagnosis. Method: A qualitative study, conducted through an open interview with people who had a late diagnosis of HIV infection. The theoretical framework adopted was the Theory of Social Representations based on a critical approach. For data analysis, was used the Structural Analysis of Narration method and the MAXQDA 12® software. Results: Eighteen people particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
(36 reference statements)
0
14
0
1
Order By: Relevance
“…Periodic screening for the virus is related to people's perception of the health-disease process and of their vulnerability to HIV, as well as to their access to the health services that offer the test (39,42) . and acting in relation to effective prevention in order not to get sick (43) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periodic screening for the virus is related to people's perception of the health-disease process and of their vulnerability to HIV, as well as to their access to the health services that offer the test (39,42) . and acting in relation to effective prevention in order not to get sick (43) .…”
Section: Discussionmentioning
confidence: 99%
“…It can be said that people diagnosed with more delay are generally those who adopt health practices that are strictly aimed at curing their illnesses, which does not exclude the influence of access barriers, including for performing the test. These individuals have problems with access to cultural goods and social development, with no possibility of reconstructing ways of thinking and acting in relation to effective prevention in order not to get sick ( 43 ) .…”
Section: Discussionmentioning
confidence: 99%
“…This hierarchy is also reflected in the idea of contamination perceived as punishment. It also seems to be based on a representation attributed to the partner as someone free from HIV infection and/or related to the representation of themselves as a person with a "clean body", that is, invulnerable to the risk of contamination and with only one partner (16) . The feeling of invulnerability of women soon turns into vulnerability in the face of HIV contamination, whether as a victim and/or guilty (7) .…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in the state of Paraiba with people who had a late or very late diagnosis of HIV infection, revealed that the risk denial was supported by a position of distance from HIV and by the frequent practice of unprotected sex, mainly due to the feeling of trust established in the relationships with only one partner or official conjugality, in which the attitude of trust was anchored in the ideas that the other does not cheat on the partner (16) .…”
Section: Discussionmentioning
confidence: 99%
“…The experiences of MSM in relation to HIV go beyond the biological aspects of the infection to include the social environment of the individual (14) . It has also been pointed out that the social representations of AIDS as a serious and incurable disease associated with death has reinforced fear and stigma, which are associated with the certainty that, once the diagnosis is confirmed, it is impossible to reverse it (15) . The perception of risk groups, mainly of the key populations of MSM, sex workers and drug users, was constructed at the beginning of the epidemic and, since then, it has generated stigma and it remains significant in the system of social representations of HIV.…”
Section: Discussionmentioning
confidence: 99%